2020
DOI: 10.1016/j.ijid.2020.01.024
|View full text |Cite
|
Sign up to set email alerts
|

An emerging public health threat: Mayaro virus increases its distribution in Peru

Abstract: Background: The infection caused by Mayaro virus (MAYV), which presents as an acute febrile illness, is considered a neglected tropical disease. The virus is an endemic and emerging pathogen in South America and the Caribbean, responsible for occasional and poorly characterized outbreaks. Currently there is limited information about its expansion and risk areas. Methods: A cross-sectional study was performed in 10 urban primary care health centers in the Cajamarca region of Peru from January to June 2017. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…These factors altogether could enable a more easily transmission of the disease. Considering previous studies on the adaptability of alphaviruses to novel vectors [32], evidence of effective MAYV transmission by more urban anthropophilic mosquitoes in laboratory studies [30,31,35], and high aedic index reported in the studied region (aedic index 1-4%) [40], these ndings may suggest that a common vector could be responsible for the transmission of both viruses during this outbreak.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These factors altogether could enable a more easily transmission of the disease. Considering previous studies on the adaptability of alphaviruses to novel vectors [32], evidence of effective MAYV transmission by more urban anthropophilic mosquitoes in laboratory studies [30,31,35], and high aedic index reported in the studied region (aedic index 1-4%) [40], these ndings may suggest that a common vector could be responsible for the transmission of both viruses during this outbreak.…”
Section: Discussionmentioning
confidence: 54%
“…Ampli cation by Real-time RT-PCR assay for the detection of MAYV was carried out using the primers and PCR conditions described by Aguilar-Luis et al [34]. Ampli cation by Real-time RT-PCR assay for DENV was described by Leparc-Goffart et al [35], and the PCR conditions were described by Alva-Urcia et al [14].…”
Section: Samplesmentioning
confidence: 99%
“…Phylogenetically, MAYV is closely related to CHIKV and, like the latter, causes a debilitating flu-like illness in the infected host that is indistinguishable from Chikungunya fever. The main symptoms include chills, fever, gastrointestinal manifestations, eye pain, myalgia and arthralgia [18,29] (Figure 2). In particular, arthralgia can last for months to years, making the Mayaro fever even more debilitating than flavivirus infections, whose symptoms last only one to three weeks [4,11,15,40,41].…”
Section: Clinical Manifestations and Pathogenesis Of Mayaro Fever In mentioning
confidence: 99%
“…After infection, MAYV causes a transient viremia which lasts 3-4 days and has an incubation period between 7 and 12 days until signs and symptoms become apparent [229]. MAYF is a disease characterized by nonspecific and self-limited sign and symptoms including fever, myalgia, arthralgia and skin rash [230] Arthralgia, headache and fever are the most common clinical manifestations and are present in the majority of symptomatic patients [231]. Rash is observed in about two thirds of the symptomatic patients and only lasts for a few days.…”
Section: Potential For Future Outbreaksmentioning
confidence: 99%
“…It is also possible that MAYV could adapt to replicate in Aedes mosquitoes causing large urban outbreaks. MAYV is present in South America [231,247,251,252] and it may also be present to a lesser extent in Central [130,253] and North America [130,254], and it is known to cause small outbreaks in areas close to forests. Adaptation to an anthropophilic mosquito vector could more readily permit sustained urban transmission.…”
Section: Potential Future Outbreaksmentioning
confidence: 99%